Dielectric Properties of 3D Printed Polylactic Acid. (17th July 2017) - Dichtl, Claudius; Sippel, Pit; Krohns, Stephan
Abstract : 3D printers constitute a fast-growing worldwide market. These printers are often employed in research and development fields related to engineering or architecture, especially for structural components or rapid prototyping. Recently, there is enormous progress in available materials for enhanced printing systems that allow additive manufacturing of complex functional products, like batteries or electronics. The polymer polylactic acid (PLA) plays an important role in fused filament fabrication, a technique used for commercially available low-budget 3D printers. This printing technology is an economical tool for the development of functional components or cases for electronics, for example, for lab purposes. Here we investigate if the material properties of "as-printed" PLA, which was fabricated by a commercially available 3D printer, are suitable to be used in electrical measurement setups or even as a functional material itself in electronic devices. For this reason, we conduct differential scanning calorimetry measurements and a thorough temperature and frequency-dependent analysis of its dielectric properties. These results are compared to partially crystalline and completely amorphous PLA, indicating that the dielectric properties of "as-printed" PLA are similar to the latter. Finally, we demonstrate that the conductivity of PLA can be enhanced by mixing it with the ionic liquid "trihexyl tetradecyl phosphonium decanoate." This provides a route to tailor PLA for complex functional products produced by an economical fused filament fabrication.